'Many Cyruses': Xenophon's "Cyropaedia" and English Renaissance Humanism Reconsidered (Revista Archai, 2021)
The reception history of a text is frequently at odds with its origins. Colin Burrow notes the irony that despite its loud support of those in power, Virgil’s Aeneid is taken up and translated by the disempowered during the Renaissance. The same is partly true of Xenophon’s Cyropaedia. This paper examines the place of the Cyropaedia within the English humanist tradition, focussing on English translations of the text, and its interpretation within the speculum principis (mirror-for-princes) tradition. This culminates in the moment when the reigning monarch, King James I of England, finds mirrored in the Cyropaedia an irresistible model of imperial kingship.